Zomermanifestatie Kunstlijn 1989. - Stichting Beeldenroute Overijssel, Dalfsen (Dalfsen : Stichting Beeldenroute Overijssel, 1989)
Klutier, Gam ; Akkerman, Ben ; van Munster, Jan ; de Groot, Kees ; Gor, Judith ; Hehenkamp, Erik ; Harding, Noël ; Kessler, David ; van de Weyer, Tine ; Tzatzalos, Eleni ; Maaskant, Jan ; Blake, John ; Armleder, John ; van Munster, Jan ; Oudshoorn, Reinoud ; Nauman, Bruce ; Wijnberg, Nicolaas ; Boezem, Marinus ; de Groot, Kees ; Gilbert & George ; Gudmundsson, Sigudur ; etc.
Zomermanifestatie Kunstlijn 1989, Stichting Beeldenroute Overijssel, Dalfsen, zomer 1989
boek